2011
DOI: 10.1107/s1600536811048550
|View full text |Cite
|
Sign up to set email alerts
|

[8-(4-Butoxybenzoyl)-2,7-dimethoxynaphthalen-1-yl](4-butoxyphenyl)methanone

Abstract: The mol­ecule of the title compound, C34H36O6, is located on a twofold rotation axis. The two 4-but­oxy­benzoyl groups at the 1- and 8-positions of the naphthalene ring system are aligned almost anti­parallel. The dihedral angles between the benzene rings and the naphthalene ring system are 71.70 (4)°. In the crystal, the mol­ecules are connected via C—H⋯π inter­actions into a layer parallel to (010).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In the course of our study on selective electrophilic aromatic aroylation of naphthalene ring core, 1,8-diaroylnaphthalene compounds have proved to be formed regioselectively by the aid of a suitable acidic mediator (Okamoto & Yonezawa, 2009. Recently, we have reported the X-ray crystal structure of 1,8-diaroyled 2,7-dimethoxynaphthalene derivatives such as 1,8-bis(4-aminobenzoyl)-2,7-dimethoxynaphthalene (Nishijima et al, 2010), [8-(4-butoxybenzoyl)-2,7-dimethoxynaphthalen-1-yl](4-butoxyphenyl)methanone [1,8-bis(4-butoxybenzoyl)-2,7-dimethoxynaphthalene] (Sasagawa et al, 2011), [2,7-dimethoxy-8-(2-naphthoyl)naphthalene-1-yl](naphthalene-2-yl)methanone [2,7-dimethoxy-1,8-bis(2-naphthoyl)naphthalene] (Tsumuki et al, 2011), and (3,5-dimethylphenyl) (Muto et al, 2012). The simplest molecule in these analogues, 1,8dibenzoyl-2,7-dimethoxynaphthalene (Nakaema et al, 2008), lies across a crystallographic 2-fold axis and the molecular…”
Section: S1 Commentmentioning
confidence: 99%
“…In the course of our study on selective electrophilic aromatic aroylation of naphthalene ring core, 1,8-diaroylnaphthalene compounds have proved to be formed regioselectively by the aid of a suitable acidic mediator (Okamoto & Yonezawa, 2009. Recently, we have reported the X-ray crystal structure of 1,8-diaroyled 2,7-dimethoxynaphthalene derivatives such as 1,8-bis(4-aminobenzoyl)-2,7-dimethoxynaphthalene (Nishijima et al, 2010), [8-(4-butoxybenzoyl)-2,7-dimethoxynaphthalen-1-yl](4-butoxyphenyl)methanone [1,8-bis(4-butoxybenzoyl)-2,7-dimethoxynaphthalene] (Sasagawa et al, 2011), [2,7-dimethoxy-8-(2-naphthoyl)naphthalene-1-yl](naphthalene-2-yl)methanone [2,7-dimethoxy-1,8-bis(2-naphthoyl)naphthalene] (Tsumuki et al, 2011), and (3,5-dimethylphenyl) (Muto et al, 2012). The simplest molecule in these analogues, 1,8dibenzoyl-2,7-dimethoxynaphthalene (Nakaema et al, 2008), lies across a crystallographic 2-fold axis and the molecular…”
Section: S1 Commentmentioning
confidence: 99%
“…For formation reactions of aroylated naphthalene compounds via electrophilic aromatic substitution of naphthalene derivatives, see: Okamoto et al (2009Okamoto et al ( , 2011. For the structures of closely related compounds, see: Hijikata et al (2010); Muto, Kato et al (2010); Sasagawa, Hijikata et al (2011); Sasagawa, Muto et al (2011); Muto, Sasagawa et al (2012). 348 parameters H-atom parameters constrained Á max = 0.21 e Å À3 Á min = À0.23 e Å À3 Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…In the course of our study on selective electrophilic aromatic aroylation of the naphthalene ring core, 1,8-diaroylnaphthalene compounds have proved to be formed regioselectively by the aid of a suitable acidic mediator (Okamoto & Yonezawa, 2009. Recently, we have reported the X-ray crystal structures of 1,8-diaroylated 2,7-dimethoxynaphthalene derivatives such as [2,7-dimethoxy-8-(4-methylbenzoyl)-1-naphthyl](4-methylphenyl)methanone [1,8-bis(4-methylbenzoyl)-2,7-dimethoxynaphthalene] (Muto et al, 2010), [2,7-dimethoxy-8-(2,4,6-trimethylbenzoyl (Sasagawa, Hijikata et al, 2011), and (Sasagawa, Muto et al, 2011). The aroyl groups in these compounds are almost perpendicularly attached to the naphthalene rings and oriented in opposite directions (anti-orientation).…”
Section: Crystal Datamentioning
confidence: 99%
“…Recently, the authors' group has found that 2,7-dialkoxynaphthalenes readily undertake acidmediated diaroylation with high peri-regioselectivity to give 1-aroyl and 1,8-diaroyl-2,7-dialkoxynaphthalenes in satisfactory yields [5,6]. In crystal, the aroyl group of the resulting molecules attaches to the naphthalene ring as nearly perpendicular manner and for diaroylated derivatives two aroyl groups are situated in opposite directions (anti-orientation) [7][8][9]. The authors' group has integrated the naphthalene-1,8-bis(carbonylarylene) unit into poly(arylene ether ketone) backbone and reported unique solubility tendency to organic solvents and characteristic thermal behavior of the resulting polymers with interpretation in relation to the spatial organization of the repeating unit [10].…”
Section: Introductionmentioning
confidence: 99%